2016
DOI: 10.5114/ada.2016.60609
|View full text |Cite
|
Sign up to set email alerts
|

Medium dose ultraviolet A1 phototherapy and mRNA expression of interleukin 8, interferon γ, and chemokine receptor 4 in acute skin lesions in atopic dermatitis

Abstract: IntroductionMechanisms responsible for UVA1 efficacy in atopic dermatitis (AD) are not fully elucidated.AimTo investigate IL-8, CCR-4, and IFN-γ mRNA expression in AD before and after UVA1, to identify correlations among them, and to determine whether and to what degree mRNA expression is influenced by UVA1.Material and methodsTwenty-five patients with AD underwent medium dose UVA1-phototherapy at daily dosages of 10, 20, 30, 45, and then continuing 45 J/cm2 up to 20 days, from Monday to Friday for 4 weeks. Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The activated monocytes also produce IL‐8 . One study showed that UVA1 irradiation reduced TNF‐α from suction blister fluid at the irradiated site compared with nonirradiated skin; however, another study demonstrated that TNF‐α increased after UVA1 irradiation in human epidermoid carcinoma cell line . TNF‐α is able to reduce type I and III collagen production by inhibiting the mRNA levels of collagens and of fibronectin, and increasing collagenase production and collagenase mRNA levels in scleroderma fibroblasts .…”
Section: Phototherapy: Mechanism Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activated monocytes also produce IL‐8 . One study showed that UVA1 irradiation reduced TNF‐α from suction blister fluid at the irradiated site compared with nonirradiated skin; however, another study demonstrated that TNF‐α increased after UVA1 irradiation in human epidermoid carcinoma cell line . TNF‐α is able to reduce type I and III collagen production by inhibiting the mRNA levels of collagens and of fibronectin, and increasing collagenase production and collagenase mRNA levels in scleroderma fibroblasts .…”
Section: Phototherapy: Mechanism Of Actionmentioning
confidence: 99%
“…TNF‐α is able to reduce type I and III collagen production by inhibiting the mRNA levels of collagens and of fibronectin, and increasing collagenase production and collagenase mRNA levels in scleroderma fibroblasts . UVA1 exposure induces keratinocytes secreting IL‐8; however, another study showed that UVA1 irradiation decreases IL‐8, IL‐6, and human beta‐defensins in the lesion of localized scleroderma . UVA1 can also induce trans‐urocanic acid (UCA) isomerization to cis‐UCA, which has immunosuppressive effects …”
Section: Phototherapy: Mechanism Of Actionmentioning
confidence: 99%
“…UVA1 phototherapy is commonly used in the treatment of immune-mediated skin diseases [ 210 ] such as atopic dermatitis, lupus erythematosus and urticaria pigmentosa. In patients with atopic dermatitis, in which the immune response is exacerbated [ 211 ], UVA1 therapy used to manage flares was found to be accompanied by a reduction in IL-5, IL-13 and IL-31 mRNA expression, an increase in the expression of IL-8 and a decrease in the serum level of eosinophil cationic protein [ 212 ]. At the cellular level, it was linked to reductions in the number of dermal LCs, activated eosinophils and mast cells and, in a relative number of intraepidermal IgE+ LCs, was linked to an increase in the percentage of dermal CD8+ T lymphocytes [ 213 ].…”
Section: Lessons Learned From Uva1 Phototherapy and The Use Of Tannin...mentioning
confidence: 99%
“…Short courses of UVA1 can be recommended for exacerbations; and for patients with severe, widespread AD, UVA with psoralen can be tried. 9,57,83,85 The choice of dosing protocols and frequency of treatment depends on the minimal erythema dose and/or the Fitzpatrick skin type and should be individualized according to the patient's characteristics, history, and symptoms. 57,83 The authors' experience suggests that phototherapy is not optimal for treating severe disease.…”
Section: Phototherapymentioning
confidence: 99%